Surviving Simulated Sepsis - Brian Hemann; Noah Hall; Jeffrey Mikita (Association of American Medical Colleges, 2010)
Abstract This is an educational resource intended to provide the information and materials necessary to run an original simulated case suitable for training small- to medium-sized groups of medical students and residents. This simulated case involves a patient presenting to the emergency department with signs and symptoms consistent with systemic inflammatory response syndrome. The trainee is responsible for proper assessment, diagnosis, and management as the patient progresses from systemic inflammatory response syndrome to sepsis, severe sepsis, and then, ultimately, septic shock. This work represents a unique style in simulation-based medical teaching. It is one of many cases developed for our fourth-year student senior medical seminars. The framework, which is based on taking care of a critical patient, pauses for discussions interspersed throughout the scenario. Typically, these occur after important decision points to illustrate and emphasize key learning objectives. Short slide sets are included with the case to facilitate these discussions. This style of teaching has helped to engage students more intimately with the material by taking advantage of the increased emotional "buy in" from the learner audience.